1976
DOI: 10.1111/j.1399-0004.1976.tb01621.x
|View full text |Cite
|
Sign up to set email alerts
|

Y/autosomal translocations

Abstract: We found six children with presumptive Y/autosomal translocation in a study of 11,148 liveborn children at the Arhus State Maternity Hospital, Denmark. The present study deals with the results of family investigation of the six children, who were found in five families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…It was found that the length of the Yq12 heterochromatic region varied in length from 29%-54% on the metaphase Y chromosome. Interestingly, the Yq12 region has also been involved in a few reported translocations (Nielsen and Rasmussen 1976;Curtis 1977). Since there are occasional translocations on the Yq12 region, it can be inferred that they might contain sequences that might induce recombination events.…”
Section: The Tripartite Element On Chromosome Ymentioning
confidence: 99%
“…It was found that the length of the Yq12 heterochromatic region varied in length from 29%-54% on the metaphase Y chromosome. Interestingly, the Yq12 region has also been involved in a few reported translocations (Nielsen and Rasmussen 1976;Curtis 1977). Since there are occasional translocations on the Yq12 region, it can be inferred that they might contain sequences that might induce recombination events.…”
Section: The Tripartite Element On Chromosome Ymentioning
confidence: 99%
“…Meiotic pairing analysis of 85 pachytene spreads showed the presence of an open structure corresponding to a quadrivalent formed by chromosomes 14, X, and the derivative chromosomes 14 and Y in 84.7% of the cases. In the remaining cases (15.3%), a 'tri- The prevalence of Y-autosome reciprocal translocations in the general human population is very low (1 in 2000) (Nielsen and Rasmussen, 1976;Powell, 1984). This kind of translocation has been observed in both fertile and sterile males (Delobel et al, 1998).…”
mentioning
confidence: 99%
“…In pigs, there are only 2 documented cases of an X-autosome reciprocal translocation as well as 2 cases of a Y-autosome reciprocal translocation [Gustavsson et al, 1989;Villagómez et al, 1991;Singh et al, 1994;Pinton et al, 2008;Barasc et al, 2012]. In humans, Y-autosome translocations are expected at a rate of 1/2,000, thus more than 100 cases are already documented [Nielsen and Rassmussen, 1976;Brisset, 2005]. Here, a carrier of a novel Y-autosome translocation identified during a systematic screening for chromosome abnormalities among 2,025 young unproven boars is reported .…”
Section: Discussionmentioning
confidence: 99%